ANALISIS PENERAPAN HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) PADA PENGOLAHAN MAKANAN DI MAINKITCHEN HYATT REGENCY YOGYAKARTA - Prasetyanto, Hermawan; Ratri, Yosephine Bayu (Sekolah Tinggi Pariwisata AMPTA, 2018)
This study aimed to analyze the application of the principles of Hazard Analysis Critical Control Points (HACCP) in food processing in the Hyatt Regency Yogyakarta main kitchen as an effort to ensure food security. The design of this study is qualitative research conducted at the Hyatt Regency Yogyakarta in May 2017. Data collection uses in-depth interviews, observations, and document studies. From the results of interviews and observations it is known that the determination of hazard identification is in accordance with HACCP provisions, the determination of critical control points (CCP) has been focused on activities that are considered critical can cause danger, have set critical limits at each critical control point established, monitoring implementation has been focused at each critical control point and monitored by the Hygiene Officer 2 (two) times per day, has established corrective actions for each critical control point that is not able to reach the critical limit, verification actions have been carried out and have been scheduled, HACCP design documentation activities and other documents have been do. The results of this study are that the application of the principles of HACCP in food processing in main kitchen has been well implemented in accordance with the standards so that it can be said that the processing of food in the Hyatt Regency Yogyakarta main kitchen has guaranteed food security for guests. Keyword: HACCP, food security, food processing, playing kitchen.